2018
DOI: 10.1111/imig.12506
|View full text |Cite
|
Sign up to set email alerts
|

Living with Compromised Legal Status: Irregular Temporary Foreign Workers in Alberta and the Importance of Imagining, Strategizing, and Inter‐Provincial Legal Consciousness

Abstract: This article highlights the manifold ways that migrants strategically use their social networks in order to survive in Alberta with compromised legal status. The conditionality of their status is affected by individual encounters and by new policy developments, showing that their ability to control their life trajectories is constrained by factors beyond their control. Nevertheless, although they experienced high amounts of stress because of their situations, the role played by cognitive processes, which inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
(28 reference statements)
0
12
0
Order By: Relevance
“…While scholars' provide grounding for research, there could be identified at least two types of rationale in the background in terms of research locality. One of them would constitute a need to address a certain (in this case marginalizing) aspect of social life -challenges related to migrants' situation as restrictive policies that placed irregular migrants in precarious situations (Tungohan, 2018) or challenges associated with low-wage work and the particular vulnerability of immigrant workers (S. Gleeson, 2010). The second aspiration for research would constitute the theoretical aspirations which focus on scientific enquiries.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…While scholars' provide grounding for research, there could be identified at least two types of rationale in the background in terms of research locality. One of them would constitute a need to address a certain (in this case marginalizing) aspect of social life -challenges related to migrants' situation as restrictive policies that placed irregular migrants in precarious situations (Tungohan, 2018) or challenges associated with low-wage work and the particular vulnerability of immigrant workers (S. Gleeson, 2010). The second aspiration for research would constitute the theoretical aspirations which focus on scientific enquiries.…”
Section: Figurementioning
confidence: 99%
“…While trying to answer the question what are the main factors informing migrant's legal consciousness and what features of legal consciousness it might bring forward the researchers addressed a broad contextual framework, ranging from evaluating cultural background (P.K. Virdi, 2013), restrictive policies and legal framework (A.A. Tungohan, 2018), societal views , institutional interaction (DoCarmo & Rosales, 2019) and welcoming countries' social norms and ideals (L. Farrell-Bryan, 2016). Though applying a lense of migrants' legal status, few factors come into the front line.…”
Section: Addressing Features Of Migrants' Legal Consciousness and Facmentioning
confidence: 99%
See 1 more Smart Citation
“…The purposeful isolation described above is just one of many examples of what Ellis and Stam [ 21 ] call “creative strategizing” (p. 11) among people without status [ 15 , 35 , 42 ]. They may find other ways to act within oppressive power structures to improve their situations [ 43 ], such as mobilizing resources and networks in order to fulfill their present and future needs [ 15 , 20 , 42 ]. Some people without status feel that working in Canada fulfills a long-held ambition and feel a sense of increased autonomy and decision-making power, seeing challenges as opportunities [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…All of the Filipino workers interviewed had not lived in the Philippines for many years and considered Canada a viable option for transitioning to PR. For these workers, accessing different PNPs through engaging in inter‐provincial migration was perceived to be a potential strategy for achieving this goal (Tungohan, 2018). With the exception of one participant originally from Mexico, all of the participants highlighted in this article come from the Philippines.…”
Section: Methodsmentioning
confidence: 99%